Sarah's unicorn - Coville, Bruce; Coville, Katherine (New York : Harper & Row, 1985)
Although she tries to keep her friendship with Oakhorn a secret, Sarah's wicked aunt finds out and is determined to rob the unicorn of his magic.
School Library Journal
2.6
K-3
Keywords: Unicorns -- Fiction; Witches -- Fiction; Unicorns -- Fiction; Witches -- Fiction